A retrospective study of the impact of DSM-5 on the diagnosis of eating disorders in Victoria, Australia. Issue 1 (December 2015) - Caudle, Henry; Pang, Christine; Mancuso, Sam; Castle, David; Newton, Richard
Abstract Background This study compares the DSM-IV and DSM-5 diagnostic criteria for eating disorders. DSM-IV resulted in a large number of patients being diagnosed with Eating Disorder Not Otherwise Specified (EDNOS). In DSM-5 the residual category is renamed Other Specified Feeding and Eating Disorders (OSFED) and Unspecified Eating Disorders (UFED) however the diagnostic criteria for the residual category in each of the diagnostic systems remains the same. This study aims to evaluate the changes in percentages of patients in a residual DSM-IV category compared to a residual DSM-5 category by retrospectively applying DSM-5 criteria to the clinical records of a patient population in a clinical setting. It also aims to compare the psychopathology between the EDNOS and OSFED/UFED groups. Methods 285 participants were recruited from a specialised eating disorder clinic in Australia over a 5-year period from 2009 until 2014. The clinical records of patients with diagnoses of anorexia nervosa (AN), bulimia nervosa (BN) and EDNOS were retrospectively assessed using the DSM-5 criteria. All patients who had attended the clinic and received an eating disorder diagnosis during this period were included in the study. No patients were diagnosed with binge eating disorder during the study period. This is surprising given the prevalence of binge eating disorder in the community. It is possible that individuals with binge eating disorder were not referred to the clinic following the initial referral and assessment due to the lack of binge eating specific interventions available. The referral process may also have been skewed towards AN, BN and EDNOS due to a perception by referring parties that binge eating disorder was a 'milder' condition that did not require specialist intervention. Information in the clinical records included structured clinical interviews, and self-rating scales of eating disorder and other psychiatric symptoms and a longitudinal narrative of patient performance and attitude during observed meals. Results We observed a 23.5% reduction in the diagnosis of OSFED/UFED with the implementation of DSM-5 compared to EDNOS with DSM-IV. The removal of Criterion D, amenorrhoea, was the leading cause for transition from EDNOS to AN. Conclusions DSM-5 has reduced the reliance on EDNOS. However this study was unable to examine the reliability of the new diagnostic criteria or the impact of DSM-5 on binge eating disorder.